2006
DOI: 10.1038/modpathol.3800599
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of dysadherin expression in epithelioid sarcoma and its diagnostic utility in distinguishing epithelioid sarcoma from malignant rhabdoid tumor

Abstract: Dysadherin is a cancer-associated cell membrane glycoprotein, which downregulates E-cadherin and promotes metastasis. We studied the clinicopathological features in 72 cases of epithelioid sarcoma and in six cases of malignant rhabdoid tumor, and also assessed the immunohistochemical expression of dysadherin, E-cadherin and MIB-1 in epithelioid sarcoma and malignant rhabdoid tumor cases. In addition, we compared dysadherin mRNA expression between epithelioid sarcoma and malignant rhabdoid tumor cell lines, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…(36) In ES, dysadherin expression was frequently observed in the proximal type, which has been reported as a more aggressive tumor compared with the distal type. (35) In synovial sarcoma, we also demonstrated that E-cadherin dysfunction caused by dysadherin expression is associated with E-cadherin repression and morphological change from the epithelioid to the spindle phenotype. (36) Concerning the diagnostic utility of adhesion molecules in STS, membranous expression of β-catenin (57) and dysadherin (35) is useful in distinguishing proximal-type ES from MRT.…”
Section: Multidrug Resistancementioning
confidence: 81%
See 4 more Smart Citations
“…(36) In ES, dysadherin expression was frequently observed in the proximal type, which has been reported as a more aggressive tumor compared with the distal type. (35) In synovial sarcoma, we also demonstrated that E-cadherin dysfunction caused by dysadherin expression is associated with E-cadherin repression and morphological change from the epithelioid to the spindle phenotype. (36) Concerning the diagnostic utility of adhesion molecules in STS, membranous expression of β-catenin (57) and dysadherin (35) is useful in distinguishing proximal-type ES from MRT.…”
Section: Multidrug Resistancementioning
confidence: 81%
“…(35) In synovial sarcoma, we also demonstrated that E-cadherin dysfunction caused by dysadherin expression is associated with E-cadherin repression and morphological change from the epithelioid to the spindle phenotype. (36) Concerning the diagnostic utility of adhesion molecules in STS, membranous expression of β-catenin (57) and dysadherin (35) is useful in distinguishing proximal-type ES from MRT. All the examined cases of proximal-type ES showed diffuse and strong membranous expression of β-catenin and dysadherin, whereas no cases of MRT had immunoreactivity for these proteins.…”
Section: Multidrug Resistancementioning
confidence: 81%
See 3 more Smart Citations